Physical optics analysis of electrically small slot-fed substrate lens antennas. - Bray, Joey R. (University of Ottawa (Canada), 1998)
With the current explosion of microwave wireless communication systems comes the need to produce low cost miniaturized components. Integrated antennas, such as planar microstrip-fed patches and slots, are a promising means of combining the antenna function with the associated transceiver circuitry. However, these antennas suffer from a bi-directional radiation pattern, power loss via substrate modes, a broad radiation pattern, or a combination of the above. To correct these problems, a dielectric lens of hemispherical shape, or slight variation thereof, can be placed directly upon the planar antenna, forming what is called a Substrate Lens Antenna (SLA). At sub-millimeter-wave frequencies, a SLA becomes unattractive because its diameter is typically larger than a free-space wavelength. Such lenses become heavy, bulky and expensive as the operating frequency is reduced. This thesis investigates electrically small, slot antenna fed, SLAs operating at 10 GHz in an attempt to facilitate the integration of these devices. (Abstract shortened by UMI.)
Keywords: Engineering, Electronics and Electrical.